SOCIAL MEDIA AND BRAND IMAGE: A STUDY ON UNKL347 CLOTHING COMP - Budiman, Arief (Universitas Pendidikan Indonesia, 2015)
It can be said that social media is a new media, a powerful media for the future. It's a media where every brand has a chance to have its own media. Its ability to encourage consumers to participate or so-called consumer generated content will make communication to be efficient, fast, and timely. The creative economy growths significantly in Indonesia. The diversity of arts, cultures, creativities of youth of the nation has now become a new era of industry in which creations with high economic value are created. Fashion is a creative work related to clothing, footwear, and fashion accessories designs, fashion and accessories production and fashion line product consulting as well as fashion product distribution. Research method used in this study is simple linear regression. The result of the study shows that social media application contributes a great impact on UNKL347's Brand Image. It is important for UNKL347 to pay attention to product quality, to give transparency on specifications and details of products offered on Social Media, to combine online and offline activations as well as to make Social Media like virtual games in order to make products being offered more interactive for customers.